ENURESIS IN SOUTHWESTERN NIGERIAN CHILDREN: PREVALENCE, RISK FACTORS AND PARENTAL PERCEPTION OF TREATMENT - Abiodun MT; Oluwafemi RO (Ntec Specialist, 2017)
Background: Enuresis means discrete episodes of urinary incontinence in a child ≥ 5 years old. It is a social stigma among older children and adolescents with possible negative effect on their self esteem and family life. Method: Enuresis was defined based on the International Children Continence Society diagnostic criteria. Structured questionnaire on basic patient information on enuresis and perceived treatment sub-scale with cronbach alpha of 0.85 was administered. Logistic regression identified predictors of enuresis The level of significance of each test was set at p less than 0.05. Results: Among the 600 participating households, 58.5% had children ≥ 5 year old with enuresis. The mean household prevalence of enuresis was 22.4% (95% CI: 11.51 - 33.25). Most of the affected households (85.5%) had one bedwetting child but 9.1% of them had two while the rest had at least three bedwetting children ≥ 5 year old. Their urinary symptoms include frequency (74.7%), urgency (14.8%), straining (8.8%) and cloudy urine (6.8%). Recent stressors among the enuretics include major illness (42.7%), relocation (32.2%) and bereavement (9.1%). Perception of enuresis therapies was borderline (mean score = 3.54± 0.5). Risk factors include parental history of bedwetting (OR=3.26, 95%CI = 1.65-6.45), monogamous family setting (OR=2.92, 95%CI = 1.38-6.18) and living in a room and parlor apartment (OR=2.19, 95%CI = 1.07- 4.50). Conclusion: There is a high burden of enuresis in the study setting, associated with some modifiable factors. However, there is a relatively low perception of appropriate care of the disorder highlighting the need for an awareness campaign on effective enuresis therapies.